DETECTION OF NITROGENASE PRODUCING BACTERIA FROM THE SOIL OF LIWA BOTANICAL GARDEN - Cristina Nugroho Ekowati; Mica Mirani; Kusuma Handayani; Rochmah Agustrina (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Liwa Botanical Gardens is an ex-situ conservation area for various types of plants. Each plant produces organic matter that will provide nutrients for the growth of nitrogen-fixing bacteria. This indicates the existence of an environment that supports the growth of nitrogen-fixing bacteria. Nitrogen is one of the nutrients needed by plants for their growth. However, the abundance of nitrogen in the atmosphere cannot be utilized directly by plants but needs to transform into ammonium and nitrate first. This transformation can be done by nitrogen-fixing bacteria through an enzymatic process. This research aims to obtain bacterial isolates that can fix nitrogen. Nitrogen-fixing bacteria were isolated using Nutrient Agar (NA) medium and furthered by nitrogenase activity detection test with semi-solid Nitrogen Free Bromothymol Blue (NFB). Nitrogen-fixing bacteria are characterized by color changes in the medium. The results obtained 22 isolates with 3 isolates detected capable of producing nitrogenase enzymes, namely TBP B3, TB1 B2, and TMA2 B2.